2016
DOI: 10.1002/jbm.a.35736
|View full text |Cite
|
Sign up to set email alerts
|

PGA-incorporated collagen: Toward a biodegradable composite scaffold for bone-tissue engineering

Abstract: Nowadays composite scaffolds based on synthetic and natural biomaterials have got attention to increase healing of non-union bone fractures. To this end, different aspects of collagen sponge incorporated with poly(glycolic acid) (PGA) fiber were investigated in this study. Collagen solution (6.33 mg/mL) with PGA fibers (collagen/fiber ratio [w/w]: 4.22, 2.11, 1.06, 0.52) was freeze-dried, followed by dehydrothermal cross-linking to obtain collagen sponge incorporating PGA fibers. Properties of scaffold for cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…investigated Raman spectrum of hydroxyapatite/gelatin composites prepared under pH 7, 8, 9, and 10 and found that a higher pH (9‐10) might lead to the dissolution of gelatin . However, no pH‐responsive modifications of Amide I, II, and III associated with the triple helical structure of collagen molecules were observed, revealing that the pH in the range of 7.9‑10.4 did not alter the second structure of collagen . Furthermore, the SDS‐PAGE patterns for the solutions at different pH were similar and displayed two α bands (110 kDa for α1 and α2) and one β band (250 kDa) (Figure S2), indicating that the collagen was not denatured with increasing pH values (7.9–10.4).…”
Section: Resultsmentioning
confidence: 99%
“…investigated Raman spectrum of hydroxyapatite/gelatin composites prepared under pH 7, 8, 9, and 10 and found that a higher pH (9‐10) might lead to the dissolution of gelatin . However, no pH‐responsive modifications of Amide I, II, and III associated with the triple helical structure of collagen molecules were observed, revealing that the pH in the range of 7.9‑10.4 did not alter the second structure of collagen . Furthermore, the SDS‐PAGE patterns for the solutions at different pH were similar and displayed two α bands (110 kDa for α1 and α2) and one β band (250 kDa) (Figure S2), indicating that the collagen was not denatured with increasing pH values (7.9–10.4).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the limited availability of donors, only a fraction of individuals who could benefit from organ transplantations actually receive them. One possible avenue for remedying this situation is to artificially engineer human tissues [44][45][46][47][48][49][50][51]. One of the central themes of tissue engineering is to reproduce the body's architectural and geometric intricacies, including vital cell-cell interactions.…”
Section: Tissue Engineering Strategymentioning
confidence: 99%
“…It should be noted that the biopolymers of PGA and PCL, which are the carrier of drug and coated on the suture, have different degradation rate. The degradation rate of PGA is higher than that of PCL [16][17][18]. We can control the degradation rate of drug-carrier by adjusting the proportion of PGA and PCL.…”
Section: Introductionmentioning
confidence: 99%